KEDUDUKAN DUNIA BAGI SEORANG MUKMIN DAN KAFIR PERSPEKTIF HADIS (METODE SYARAH HADIS BI AL-MA’TSUR) - Darojatun Hasanah; Rihhadatul Aisy Amry; Shinta Nurdia Devi KHN; Silviya Zukhruf Aini; Reza Pahlevi Dalimunthe (Jurnal Studi Hadis Nusantara, 2022)
This article aims to discuss the sharah hadith concerning the position of the worldfor humans, especially for believers and unbelievers. In a hadith it is stated thatthe world is a prison for believers and heaven for unbelievers, generally prison isoften defined as suffering while heaven is defined as pleasure. But in fact there aremany believers whose lives are happy and far from suffering as well as unbelievers,not all of whom live happily. With the syarah bi al-ma'tsur method, this study willdiscuss how the real position of this world is for believers and unbelievers. Theresult of the explanation of bil matsur for this hadith is that the world is like aprison for believers because in living their lives they have limits according to theprovisions of Allah Almighty, and the enjoyment that believers get in the world islike a prison because in the hereafter the enjoyment that is obtained is in the form ofHis heaven is far away. better value than in the world. while the world is like heavenfor unbelievers because in living their lives they are free to do anything and Allah'sreward in the afterlife in the form of hell for them is far more sad and terrible thantheir sorrow in the world.